Comprehensive Assessment of Indexes of Statics, Dynamics and Intensity of the Ukrainian regions’ Development in 2015 - Kulynych, O. I. (Statistics of Ukraine, 2016)
Each country, region or business enterprise needs comprehensive assessment of the socio-economic development. Justification of the reasonability and necessity for systematization of the contemporary statistical methodology for assessment of correlations of socio-economic development indexes at regional level, being important and relevant, requires the developed assessment methodology and statistical tools focused on quantitative description of the existing socio-economic development at regional level. Statistical studies of correlations of socio-economic development indexes, computed by use of regional data, enable for modeling of processes taking place at country and regional level, to find the nature of structural change and predict its consequences. The method for ranking of the Ukrainian regions by indexes of statics, dynamics and intensity of socio-economic development in 2015 by use of the method of complex statistical coefficients is proposed. The main problems solved by the method of complex statistical coefficients through standardizing the values of the studied indexes irrespective of their expression form (absolute values, ratios or mean values of statics and dynamics, or ratios of dynamics and fulfillment of plan) are ranking of regions by socio-economic development (business and financial performance of enterprises) in a given period; the ranks can be used for taking sound decisions on performance enhancement for the entities with bottoms ranks in the overall rating; when variational series are used, the ranks of the entities under study can be found; when the dynamic series are used, the ranks of the entities over periods of time covered by the study can be found, to determine the rhythm in time. The method for comprehensive assessment uses data from the current statistical reporting; no other data are required. It can be used for comprehensive assessment of results at micro- and macrolevel. The comprehensive assessment is significant inasmuch as it helps develop approaches to improve the quality of planning and management. Use of complex statistical coefficients for characteristics of economic activities or regions is a necessary condition of this important objective.